2010
DOI: 10.1093/nar/gkq1050
|View full text |Cite
|
Sign up to set email alerts
|

5′-end surveillance by Xrn2 acts as a shared mechanism for mammalian pre-rRNA maturation and decay

Abstract: Ribosome biogenesis requires multiple nuclease activities to process pre-rRNA transcripts into mature rRNA species and eliminate defective products of transcription and processing. We find that in mammalian cells, the 5′ exonuclease Xrn2 plays a major role in both maturation of rRNA and degradation of a variety of discarded pre-rRNA species. Precursors of 5.8S and 28S rRNAs containing 5′ extensions accumulate in mouse cells after siRNA-mediated knockdown of Xrn2, indicating similarity in the 5′-end maturation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
118
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(135 citation statements)
references
References 61 publications
(88 reference statements)
14
118
0
3
Order By: Relevance
“…S10D, probe hITS1b) processing intermediates, which are normally eliminated from the cell by the 5 0 -3 0 exoribonucleolytic activity of hXRN2. 11,36 However, in agreement with the primer extension results, hXRN2 silencing did not significantly influence any of the phenotypes associated with hUTP24 mutation.…”
supporting
confidence: 87%
“…S10D, probe hITS1b) processing intermediates, which are normally eliminated from the cell by the 5 0 -3 0 exoribonucleolytic activity of hXRN2. 11,36 However, in agreement with the primer extension results, hXRN2 silencing did not significantly influence any of the phenotypes associated with hUTP24 mutation.…”
supporting
confidence: 87%
“…The combined endo-and exonucleolytic activities of Rrp44 (Dis3) are responsible for degradation of the fragment between the A0 site and at the 5 ′ end of the pre-rRNA (Lebreton et al 2008;Schaeffer et al 2009;Schneider et al 2009), while a fragment generated by cleavages at A0 and the 5 ′ end of the mature 18S rRNA accumulates when Rat1 is deleted (Petfalski et al 1998). Similar roles for the mouse homologs of these enzymes have been suggested (Kent et al 2009;Wang and Pestov 2011), but 5 ′ ETS fragment turnover and aberrant pre-rRNA degradation have not been described in human cells.…”
Section: Introductionmentioning
confidence: 69%
“…The major nuclear 5 ′ to 3 ′ exonuclease XRN2 is important for A ′ cleavage in several different organisms (ZakrzewskaPlaczek et al 2010;Wang and Pestov 2011;Sloan et al 2013b) and has also been shown to be important for turnover of the 5 ′ ETS fragment generated by this cleavage in mouse cells (ETS1) (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process was mainly characterized in yeast and, surprisingly, only recently investigated in human cells, revealing that pre-rRNA processing pathways are notably different in metazoan: ∼27% of human factors have distinct or additional functions in pre-rRNA processing compared with their yeast orthologs, and several pre-RNA processing factors have no yeast homolog (26,29). XRN2 (homolog of yeast XRN2/Rat1) plays a major role in rRNA maturation, coordinating the optimal order of multiple pre-rRNA cleavages (25); it is essential for degradation of 5′-extended 45.5S and 34.5S pre-rRNAs forms, it removes ITS-1-derived extensions to generate 32S from 32.5S pre-rRNA, and it promotes decay of 5′-01, 5′-A0, and E2 fragments, generated by endonucleolytic cleavages in the 5′ETS/ITS1 region in human cells (27)(28)(29) (Fig. 4A).…”
Section: Resultsmentioning
confidence: 99%